1986
DOI: 10.1002/jor.1100040305
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic studies of the lumbar trunk musculature during the development of axial torques

Abstract: Summary:The myoelectric activity of selected trunk muscles at the L3 level was studied during the development of a controlled isometric axial torque. Muscle activity was recorded with surface electrodes bilaterally over the erector spinae muscles, the rectus abdominus, the obliques externus, and the obliques internus. Subjects applied graded isometric axial torque efforts with the addition of a Valsalva. The largest myoelectric activities were recorded over the obliques externus and internus. The side of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 17 publications
4
36
1
2
Order By: Relevance
“…This finding was similarly demonstrated in some previous studies [27,28,49] but not in another study by Pope et al [39]. One of the reasons may be due to the EMG data of Pope et al's study [39] not being normalized, so the comparison between muscles may not be the same as other studies where normalization of the EMG data occurred.…”
Section: % --supporting
confidence: 64%
See 1 more Smart Citation
“…This finding was similarly demonstrated in some previous studies [27,28,49] but not in another study by Pope et al [39]. One of the reasons may be due to the EMG data of Pope et al's study [39] not being normalized, so the comparison between muscles may not be the same as other studies where normalization of the EMG data occurred.…”
Section: % --supporting
confidence: 64%
“…Conflicting results on the activity of' abdominal and back muscles have been demonstrated in these previous studies because of different experimental procedures. For example, Pope et al [39] found that there was no difference in activity (non-normalized EMG data) between ipsilateral and contralateral internal oblique. On the other hand, Thelen et al [49] demonstrated higher activity (normalized EMG data) in ipsilateral internal oblique than that of contralateral side.…”
Section: Ct Al I Journul Of Orthopuedic Riwarch 19 (-7001 I 463471mentioning
confidence: 99%
“…Granata and England [12] emphasized the stabilizing effect of the activity of the oblique muscles in asymmetrical tasks. Trunk twisting indeed coincides with high levels of trunk muscle cocontraction, due to the side effects that the oblique abdominal muscle have in other planes [26][27][28][29]. In line with this explanation, Graham et al [14] showed that a load carried in the hands, which causes an increase in trunk muscle activity, coincided with higher LDS in the same trunk movement.…”
Section: Discussionmentioning
confidence: 89%
“…Adams and Hutton [3] have shown that in forward flexion the disc is less tolerant to compression and the facet joints may disengage, allowing greater torsion on the intervertebral disc, placing the discs fibers in a position much more vulnerable to injury [65,70].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason many lifting guides, including the NIOSH guide, suggest that all lifting occur between knee and shoulder level, where the trunk muscles are close to their resting length. Significantly greater concurrent muscle activation and loading occur during twisting motions of the trunk as a strategy to enhance trunk stability [65]. However, this coactivation increases loading, because the antagonist muscles in the trunk must compete with the agonist muscles.…”
Section: Introductionmentioning
confidence: 99%